2016
DOI: 10.5937/geopan1603161d
|View full text |Cite
|
Sign up to set email alerts
|

East Sarajevo (Bosnia and Herzegovina) twenty years later: Changes in land use

Abstract: The city of East Sarajevo is a newborn city, formed twenty years ago, after the war in Bosnia and Herzegovina, in the area of the former southern and eastern Sarajevo municipalities. Changes that occurred in this area were not only administrative-political.Thepopulation moved from one area to another place, and changed in number and structure, which has resulted in significant changes in land use and land cover types. The aim of the paper is to analyze the types of land cover in the area of East Sarajevo using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…This indicates that artificial surfaces increased their spatial coverage by 15.51 km 2 over eighteen years, primarily at the expense of agricultural areas, particularly complex cultivation patterns (at the level of code 2.4.2) and land principally occupied by agriculture, with significant areas of natural vegetation (at the level of code 2.4.3). Geographically, the urban development of the Sarajevo valley, especially the expansion of artificial surfaces, intensified notably in specific municipalities, led by Ilidža, Vogošća, and Novi Grad Sarajevo, as well as certain locations within Istočno Sarajevo (Drašković et al, 2016). The expansion of economic locations, infrastructure development, and residential construction are the primary drivers of these spatial changes.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that artificial surfaces increased their spatial coverage by 15.51 km 2 over eighteen years, primarily at the expense of agricultural areas, particularly complex cultivation patterns (at the level of code 2.4.2) and land principally occupied by agriculture, with significant areas of natural vegetation (at the level of code 2.4.3). Geographically, the urban development of the Sarajevo valley, especially the expansion of artificial surfaces, intensified notably in specific municipalities, led by Ilidža, Vogošća, and Novi Grad Sarajevo, as well as certain locations within Istočno Sarajevo (Drašković et al, 2016). The expansion of economic locations, infrastructure development, and residential construction are the primary drivers of these spatial changes.…”
Section: Resultsmentioning
confidence: 99%
“…CORINE Land‐Cover, starting from 1990, has provided valuable information on land cover in 44 different classes (Büttner et al, 2004). Twenty years after the C ity's formation, East Sarajevo, a city formed after the war in Bosnia and Herzegovina, the land‐cover changes affecting the City were analyzed using CORINE data in the period from 2000 to 2012 (Drašković et al, 2016). As expected, significant increases happened in the urban areas on account of low‐productive grassland and mixed forest vegetation.…”
Section: Resultsmentioning
confidence: 99%
“…Analysing the periods, higher intensity of changes occurred over the period from 2000 to 2006 and from 2012 to 2018 compared to the period from 2006 to 2012. According to the inter-period spatial changes, it was found that the intensity of urbanization gradually reduced and in the future it can be expected to continue this downward trend because the migration population is greatly reduced in comparison to the first decade of the twenty-first century (Drašković, Drešković, & Mirić, 2016). Table 1).…”
Section: Resultsmentioning
confidence: 99%